2020
DOI: 10.18616/inova.v9i2.4043
|View full text |Cite
|
Sign up to set email alerts
|

Auriculoterapia No Controle Da Ansiedade De Mulheres Menopausadas

Abstract: Estudo com objetivo de conhecer a percepção das mulheres sobre a contribuição da Auriculoterapia na Ansiedade. Pesquisa de abordagem qualitativa, descritiva, exploratória e de campo. O estudo foi desenvolvido com 16 mulheres menopausadas atuantes como auxiliar de limpeza da Universidade do Extremo Sul de Santa Catarina - UNESC. Aplicou-se o Índice de Menopausa de Kupperman e Blatt e Escala de Avaliação de Ansiedade de Hamilton; 08 sessões de auriculoterapia e a entrevista semiestruturada. Em relação ao índice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…It was also found that after four weeks of treatment with auriculotherapy, 89.42% of patients already demonstrated a reduction in anxiety levels, confirming previous studies. A field study with a qualitative approach, using the Hamilton Anxiety Rating Scale, with ear points Kidney, Shenmen , Heart, and Anxiety, for eight weeks, showed that auriculotherapy reduced participants’ anxiety levels by 71.43% ( 28 ) . In Cuba, an experimental study on a therapeutic intervention carried out with 100 patients with anxiety disorder, divided into a study group and a control group, using the points Shenmen , Heart, Kidney, and Zero Point, showed that 92% of patients reported remission of almost all anxiety symptoms after four weeks of treatment ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that after four weeks of treatment with auriculotherapy, 89.42% of patients already demonstrated a reduction in anxiety levels, confirming previous studies. A field study with a qualitative approach, using the Hamilton Anxiety Rating Scale, with ear points Kidney, Shenmen , Heart, and Anxiety, for eight weeks, showed that auriculotherapy reduced participants’ anxiety levels by 71.43% ( 28 ) . In Cuba, an experimental study on a therapeutic intervention carried out with 100 patients with anxiety disorder, divided into a study group and a control group, using the points Shenmen , Heart, Kidney, and Zero Point, showed that 92% of patients reported remission of almost all anxiety symptoms after four weeks of treatment ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Na auriculoterapia, aplica-se o estímulo em pontos que se relacionam diretamente com o cérebro, e este por sua vez atua de forma reflexa sobre os órgãos e suas funções 41 . Estudos apresentam resultados positivos em relação à eficácia da auriculoterapia como método alternativo para o combate do estresse, ansiedade e depressão, podendo assim colaborar na redução da ansiedade frente ao tratamento odontológico 11,18,19 .…”
Section: Auriculoterapiaunclassified
“…A MTC considera que os aspectos psicoemocionais, em especial o estresse, podem provocar uma má distribuição energética nos meridianos (canais por onde circula o Qi), nos órgãos e vísceras, desencadeando doenças físicas, mentais e emocionais (Lemos et al, 2019). Nesse sentido, a prática da auriculoterapia é recomendada para o tratamento de condições agudas, crônicas e mentais, incluindo doenças como a fibromialgia (Garcia et al, 2019;Tesser et al, 2019).…”
Section: Introductionunclassified